Enhanced piezoelectricity and high-temperature sensitivity of Zn-modified BF-BT ceramics by in situ and ex situ measuring. Issue 4 (March 2017) - Tong, Kai; Zhou, Changrong; Wang, Jun; Li, Qingning; Yang, Ling; Xu, Jiwen; Zeng, Weidong; Chen, Guohua; Yuan, Changlai; Rao, Guanghui
Abstract: Effect of Zn addition on microstructure, electrical properties and temperature stability and sensitivity of piezoelectric properties for 0.7Bi1- x Zn x FeO3 −0.3BaTiO3 (abbreviated as BZ x F–BT) ceramics was investigated. The improved piezoelectric properties, high-temperature stability and high-temperature sensitivity by in situ and ex situ measuring were obtained by moderate Zn addition. It was demonstrated that the enhancement piezoelectric properties can be attributed to poling induced texturization degree of ferroelectric domains and increased rhombohedral structural distortions. It was proposed that the depoling temperature where the induced small signal piezoelectricity disappears stemmed from the detexturization of preferred orientation domains. The improved piezoelectric responses and high-temperature sensitivity could be attributed to the thermally activated preferred orientation domains. The good piezoelectric properties together with high-temperature stability suggest that BZ x F–BT system is a promising material for high temperature piezoelectric applications.